Tahfidz Al-Quran Learning Methods With Superior Class Programs - Chew, Maykoski; Murat, Ritacco; Justine, Kose (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Tahfidz learning is a learning that is carried out between students and teachers to change student behavior and improve Al-Quran memorization. Rumah Tahfidz is an activity where learning to memorize the Al-Quran, practice and apply the values ??of the Al-Quran which are carried out in daily life can be in residential homes, campuses and schools. The purpose of this research is to 1). Knowing how the activities of the Tahfidz Al-Quran program are at the MQM Batusangkar Quran House. 2). Knowing how the method of implementing the Tahfidz program at the MQM Batusangkar Quran House 3). Knowing the supporting and inhibiting factors for the implementation of the Tahfidz Program at the MQM Batusangkar Quran House. In this study it is known that 1). Tahfidz activities are held from Monday to Friday every ba'da asar until half past six, where the activities initially start here by praying first then students listen to directions from the Tahfidz teacher and are given a few minutes to prepare their respective memorization to be deposited, after all students deposit their memorization followed by several games such as the verse connecting game, and guessing the letter immediately closed with a prayer, then the teacher and students prepare for the next material lesson. 2). The methods for implementing the Tahfidz Program at the MQM Batusangkar Quran House are the Wahdah Method, Kitabah Method, Sima'i Method, and Murajaah Method. 3). supporting and inhibiting factors for the implementation of the Tahfidz Program at the MQM Batusangkar Quran House, namely student interests, student talents, parents, teachers, the community and the surrounding environment and also equipped with several media images when teaching Tahfidz. While the inhibiting factor is the ability of the students themselves because there are some abilities that are below average, so the teacher has to be more extra in teaching with various methods.